2000
DOI: 10.1023/a:1009905808033
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A brief overview of the most important steps leading to our present knowledge of hypercorticism is given. The adrenals were described in 1563 and the pituitary had been known since Antiquity. Until Addison's description of adrenal insufficiency in 1855 virtually nothing was known of their function. Cushing in 1912 described his famous patient with hypercorticism but assumed it to be a polyglandular disorder. For almost 40 years the etiology was disputed, though Bauer early had postulated that hypercorticism ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…As indicated in figure 7, the peaks in the CS + 2 B(0 0 1) 2 + g → X(0 0 1) 2 u fluorescence excitation spectrum can, in principle, be ascribed to three Rydberg series, with quantum defects (δ) of ∼0.05, 1.7 and 2.3. These values are typical for series associated with second row atoms [26][27][28] and are similar to those corresponding to the well-established vibrationally unexcited Rydberg series in CS 2 [24,25]. Five members can be assigned to the δ ∼ 0.05 series, and these include the intense peak at 14.877 eV.…”
Section: Vibrationally Resolved Fluorescence Excitation Spectrasupporting
confidence: 72%
See 1 more Smart Citation
“…As indicated in figure 7, the peaks in the CS + 2 B(0 0 1) 2 + g → X(0 0 1) 2 u fluorescence excitation spectrum can, in principle, be ascribed to three Rydberg series, with quantum defects (δ) of ∼0.05, 1.7 and 2.3. These values are typical for series associated with second row atoms [26][27][28] and are similar to those corresponding to the well-established vibrationally unexcited Rydberg series in CS 2 [24,25]. Five members can be assigned to the δ ∼ 0.05 series, and these include the intense peak at 14.877 eV.…”
Section: Vibrationally Resolved Fluorescence Excitation Spectrasupporting
confidence: 72%
“…To conclude this tentative interpretation of the B(0 0 1) 2 + g → X(0 0 1) 2 u fluorescence excitation spectrum, the series with δ ∼ 0.05 can plausibly be associated with one of the nd Rydberg series, in accord with the assignment proposed by Hikosaka and Mitsuke [8]. In atomic sulfur, quantum defects of ∼2, 1.6 and 0.3 have been obtained for s, p and d type series, respectively [27,28]. Therefore, the series in figure 7 having δ ∼ 2.3 might be ascribed to the dipole allowed nsσ g transitions.…”
Section: Vibrationally Resolved Fluorescence Excitation Spectrasupporting
confidence: 54%
“…This penetration results in the effective nuclear charge becoming greater than unity so that an electron in a penetrating orbital will be more tightly bound than one in a non-penetrating orbital. For polyatomic molecules built-up from atoms of the first period, δ is small ( 0.1) for states involving nd electrons, somewhat larger (0.3-0.6) for np electrons and appreciably larger (0.9-1.2) for ns electrons [12].…”
Section: Introductionmentioning
confidence: 94%
“…The debate concerning the roles of the pituitary and adrenal in Cushing syndrome persisted [16] until about 1950, when Julius Bauer [17] concluded that both the pituitary and the adrenal can separately cause “the so-called Cushing’s syndrome” and proposed that the term “Cushing’s disease” be reserved for the pituitary form. The history of Cushing syndrome was reviewed recently [18]. …”
Section: The Glandsmentioning
confidence: 99%